Psychology and humanistic psychotherapy - Amorós, Víctor (1996)
The article is about the origins of rhe humanistic and psychological orientation, its principal characteristics like our capacity to choose and modify our vital situation, to be orienred to the action of the values that give us identity and permit us unroll an active ego that in spite of rhe conditionant influence elaborare a self evolution. Ir analyses the concept of self realization and the way that psychorerapy process takes place.